Sequence detection of coded signals for high density storage channel - Li, Yi Ping. (2010)
The storage of very high density data is required in the hard-disk industry today. To increase the storage density, the early research work focused on the media material and read-back machine, which is restricted by the user bit density. However, many techniques used in communications involve read-back signal processing. Some such techniques include modulation coding, equalisation and sequence detection. Also, Run-length-limited (RLL) codes are popularly used in storage channel. To reduce the noise power at the input of the detector, the Whitened Matched Filter (WMF) is applied to the read-back signal generated by the head of hard-disk driver. In this project, the aim is to study and simulate hard-disk read-back signal processing, and then evaluate different signal detectors. So, this thesis describes not only RLL code and WMF, but also various signal detectors.